2010
DOI: 10.1186/1750-1326-5-57
|View full text |Cite
|
Sign up to set email alerts
|

Conformation dependent monoclonal antibodies distinguish different replicating strains or conformers of prefibrillar Aβ oligomers

Abstract: BackgroundAge-related neurodegenerative diseases share a number of important pathological features, such as accumulation of misfolded proteins as amyloid oligomers and fibrils. Recent evidence suggests that soluble amyloid oligomers and not the insoluble amyloid fibrils may represent the primary pathological species of protein aggregates.ResultsWe have produced several monoclonal antibodies that specifically recognize prefibrillar oligomers and do not recognize amyloid fibrils, monomer or natively folded prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 30 publications
7
153
0
Order By: Relevance
“…Comparison of LFAOs with Other Oligomers Indicates Similarities and Differences-There are only a handful of reports on the replication property of A␤ oligomers, and of those, the reports by Glabe and co-workers (20,28,37) are the most recent. They identified three specific soluble oligomer subtypes classified mainly on the basis of their immunoreactivity toward conformation-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of LFAOs with Other Oligomers Indicates Similarities and Differences-There are only a handful of reports on the replication property of A␤ oligomers, and of those, the reports by Glabe and co-workers (20,28,37) are the most recent. They identified three specific soluble oligomer subtypes classified mainly on the basis of their immunoreactivity toward conformation-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…They identified three specific soluble oligomer subtypes classified mainly on the basis of their immunoreactivity toward conformation-specific antibodies. These subtypes are PFOs, fibrillar oligomers (FOs), and APFs, and they are recognized by the conformation-specific antibodies A11, OC, and ␣PF, respectively (28). Among these, both PFOs and FOs showed a self-replication property by converting monomers into oligomers of the same type (28,38).…”
Section: Discussionmentioning
confidence: 99%
“…7B, all CRES subgroup proteins possessed structures characteristic of amyloid including bundles of fibrils, protofibrils with a beads-on-a-string appearance (CRES), large branched polygons (CRES3) and bundles of fibrils/films assembling into higher ordered structures (CRES2, cystatin E2). Recombinant proteins diluted into aqueous buffer were also examined for amyloid by spotting the samples on to nitrocellulose and carrying out dot blot analysis using conformation-dependent antibodies that recognize the immature forms of amyloid (anti-oligomer A11 antibody) and the mature forms of amyloid (anti-fibrillar OC antibody) (Kayed et al, 2010). The antifibrillar OC antibody bound to all CRES subgroup proteins suggesting the presence of amyloid fibrils, while A11 bound only to CRES and cystatin E2 suggesting they also contained earlier, less mature, forms of amyloid including protofibrils and oligomers (Fig.…”
Section: Cres Subgroup Proteins Form Amyloid In Vitro and In Vivomentioning
confidence: 99%
“…A breakthrough in this area has been the development of conformation-specific antibodies that selectively recognize uniquely folded conformers of amyloidogenic proteins (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Indeed, multiple conformation-specific antibodies have been reported that recognize structural features within amyloidogenic oligomers (5) and fibrils (4,6,8) in a sequence-independent manner.…”
mentioning
confidence: 99%